SOME CHARACTERISTICS OF RELIGIOSITY OF THE STUDENT POPULATION (Annual of the Faculty of Philosophy in Skopje, 2009)
In this paper are analysed the results of an empirical research on religiosity of the student population in the Republic of Macedonia, more precise the students from Ss. Cyril and Methodius University in Skopje. This research is a part of a research project on the identity of Macedonians in conditions of transition and globalisation.The results of this research confirm the high level of religiosity and show a state of religiosity of the student population with a high level of inconsistency in all components of its fulfilment. The student population dramatically is looking for an authenticity of the sacred understood, but emotionally and practically experienced, which in a great measure is stimulated by the dramatization of the changes in all segments of the human life in the last twenty years. A type of „religious man" who tries to combine elements of religiosity typical for different types has been noticed, if we compare the results of our research of the student population in general with the investigation of the religiosity of the population especially young generation with similar researches made on the territory of the former Yugoslav state, it could be seen that there is no big differences in the level and characteristics of the religiosity compared with all elements that form it.
Keywords: STUDENTS; RELIGIOSITY VALUES; REVITALIZATION OF RELIGION; POSTSOCIALISM